Norsk dataterminologi - Undersøkelse av norske avløserord og engelske importord i fagtekster og populærfaglige tekster innen dataområdet før og nå - Aarflot, Anne Helene (Nordiske Studier i Leksikografi, 2003)
I will present some preliminary results of my research in connection with a thesis concerning the development of Norwegian computer terminology. I will give some examples of Norwegian computer terms that have been successfully integrated in Norwegian everyday language and technical language during the last decade, and describe a few characteristic traits of the computer terms that currently are being used in Norwegian.